Servo Board: Type 5131 - Technical Description - Hps SystemTechnik
The Servo board contains a DC motor wich is coupled to a potentiometer by a gear The potentiometer is used for analog position location To protect the potentiometer, its wiper is decoupled through an amplier. The signal is available in invented form at the output. The motor of the Servo board can be controlled digitally in both directions of rotation by TTL inputs and a series circuited logic. This makes digital control of the servo board possible......